Analisis Non Performing Loan Untuk Menilai Profitabilitas Pada Bank Rakyat Indonesia (Persero) Tbk yang Terdaftar di BEI Periode 2021-2023 - Wihelmina Maryetha Yulia Jaeng (Pusat Riset dan Inovasi Nasional, 2024)
A State-Owned Enterprise is a business entity whose capital is largely owned by the state. Thus, all BUMN activities are generally supervised by the state. The aim of this research is to find out and explain NPL in assessing profitability at BRI (Persero)Tbk which is listed on the IDX for the 2021-2023 period. The ratios used in assessing profitability are ROA, ROE, NPM. This research method uses a quantitative descriptive approach. The results of this research show that the NPL from 2021 is 3.08%, in 2022 it is 2.82% and in 2023 it is 3.12%, while ROA, ROE and NPM have increased over the three years. NPL at BRI (Persero) Tbk registered on the IDX for the 2021-2023 period experienced increases and decreases in the good category of ≤ 5% and the banking ability to generate profits was measured based on profitability ratios.